2007
DOI: 10.1038/npre.2007.1394.1
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of intrinsic disorder in SV-IV, a multifunctional androgen-dependent protein secreted from rat seminal vesicle

Abstract: The potent immunomodulatory, anti-inflammatory and procoagulant properties of the protein no. 4 secreted from the rat seminal vesicle epithelium (SV-IV) have been previously found to be modulated by a supramolecular monomer-trimer equilibrium. More structural details that integrate experimental data into a predictive framework have recently been reported. Unfortunately, homology modelling and fold-recognition strategies were not successful in creating a theoretical model of the structural organization of SV-IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Studies conducted over the last decade showed that approximately one-third of all eukaryotic proteins contain disordered regions 6 . IDPs perform various functions due to their ability to recognize and selectively bind multiple partners 7 8 9 . TROSPA from ticks belonging to Ixodidae has been reported to interact with at least two pathogen-derived effectors 2 3 4 .…”
mentioning
confidence: 99%
“…Studies conducted over the last decade showed that approximately one-third of all eukaryotic proteins contain disordered regions 6 . IDPs perform various functions due to their ability to recognize and selectively bind multiple partners 7 8 9 . TROSPA from ticks belonging to Ixodidae has been reported to interact with at least two pathogen-derived effectors 2 3 4 .…”
mentioning
confidence: 99%